Admixture dynamics in Hispanics : A shift in the nuclear genetic ancestry of a South American population isolate (2006)
ABSTRACT: Although it is well established that Hispanics generally have a mixed Native American, African, and European ancestry, the dynamics of admixture at the foundation of Hispanic populations is heterogeneous and poorly documented. Genetic analyses are potentially very informative for probing the early demographic history of these populations. Here we evaluate the genetic structure and admixture dynamics of a province in northwest Colombia (Antioquia), which prior analyses indicate was founded mostly by Spanish men and native women. We examined surname, Y chromosome, and mtDNA diversity in a geographically structured sample of the region and obtained admixture estimates with highly informative autosomal and X chromosome markers. We found evidence of reduced surname diversity and support for the introduction of several common surnames by single founders, consistent with the isolation of Antioquia after the colonial period. Y chromosome and mtDNA data indicate little population substructure among founder Antioquian municipalities. Interestingly, despite a nearly complete Native American mtDNA background, Antioquia has a markedly predominant European ancestry at the autosomal and X chromosome level, which suggests that, after foundation, continuing admixture with Spanish men (but not with native women) increased the European nuclear ancestry of Antioquia. This scenario is consistent with historical information and with results from population genetics theory.